ADDED VALUE OF ROBUSTA COFFEE PROCESSING IN BANG MOEL COFFEE HOME INDUSTRY INDIFFERENT PACKAGING - Alfiyah, Siti; Puryantoro, Puryantoro; Untari, Wiwik Sri (Program Studi Agribisnis Fakultas Pertanian, 2024)
The added value of processing coffee beans into robusta coffee powder and using different packaging, namely labeled plastic packaging, and clear plastic packaging, will of course bring benefits to these entrepreneurs. Therefore, it is necessary to discussin more detail to find out the added value obtained by the robusta coffee powder processing business in the Bang Moel Kopi household industry. This study aims to determine the added value obtained from the processing of robusta coffee powder in the household industry of Bang Moel Kopi in producing coffee powder. In this study, the analysis used is the hayami analysis method. The results of the study show that the value-added ratio of label packaging robusta coffee powder is in a high value-added positionbecause it is >40%, while the value-added ratio of plastic packaging is in the value-added category while curry has a percentage of 15-40%.